Hubungan Indeks Massa Tubuh Dengan Resiko Low Back Pain Pada Pasien di Klinik Fisioterapi Singgasana Rama Blitar - Risa Puspita Sari; Fransisca Xaveria Hargiani; Wahyu Teja Kusuma; Nurul Halimah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: Low Back Pain patient in Physiotherapy Clinic of Singgasana Rama Blitar City during the span of January 2020 until December 2020 showed that 32% of the visitor suffer low back pain issue. There are several reason behind low back pain and one of them is overweight issue that result on pressure in the vertebra lumbal become higher thus disturb the structure of the backbone. Body mass index is measurement method that compare the weight and the height of someone to determine their body proportion whichever they are underweight, normal, overweight or obesity.Methods: The method used on this study is observational analytic with sampling method that been used is purposive sampling. Data that used on this study is data that have been acquired from survey that consist of their gender, age, job, and the supporting data which is their x-ray, pain scale in the form of numeric rating scale (NRS), height and weight. The data that have been gathered then will be processed into analytic data.Results: From the result of study between 50 people that fulfill inclusion criteria we get result that body mass index category of normal is 16%, overweight 28%, and obesity 56%. Meanwhile NRS score value 4 is 22% value 5 is 16%, value 6 is 30%, value 7 is 20% and value 8 is 12%. According to correlation test we know that the value of Sig. (2 tailed) between body mass index (X) and NRS (Y) is 0,02<0,05, which mean H0 is rejected, and there are significant relation between body mass index and NRS. Pearson correlation value is 0,425 more than 3-table which is 0,279 which mean relationship between two variable is positive.Conclusion: Body mass index have significant relation with low back pain, in another word the higher the mass body index the higher the risk of getting low back pain